Determinants of Smoking Behaviour Among Indonesian Elementary School Students: A Cross-Sectional Study - Hidayah, Rizka Nurul; Jason, Jason; Sakina, Sakina; Syulthoni, Zain Budi; Syafira Eljatin, Dwinka (Riviera Publishing, 2025)
Indonesia faces a critical public health challenge with one of the highest smoking rates globally, including among elementary school children. Understanding the determinants of this early smoking behavior is essential for developing effective prevention strategies. This study, Determinants of Smoking Behaviour Among Indonesian Elementary School Students: A Cross-Sectional Study, aimed to identify the factors associated with smoking behavior among elementary school students in Bojonegoro Regency, Indonesia. A cross-sectional study was conducted using secondary data from a Ministry of Health survey. The sample consisted of 1,071 students from grades 4–6 across 20 elementary schools, selected via total population sampling. Data were analyzed using Chi-square tests to examine associations between smoking status and variables such as gender, grade level, knowledge, and environmental exposure. The prevalence of ever having smoked was 8.7%, exclusively among boys. Significant risk factors (p < 0.01) included being male, higher grade level, having smoking family members, having peers who smoke, and witnessing people smoke at school—notably, teachers and community members. Surprisingly, children who knew the dangers of smoking had a higher smoking prevalence. Smoking behavior in elementary students is strongly influenced by environmental exposure and gender. Prevention requires a multi-faceted approach, including strict smoke-free policies in schools, targeted anti-smoking education for boys, and community-wide interventions to reduce children's exposure to smoking role models.